Antifungal, phyto, cyto, genotoxic and lipophilic properties of three complexes of sulfadimethoxine (HSDM) with Ag(I). Synthesis and characterization of [Ag3SDM(SCN)2]·H2O and [Ag2(SDM)2o-phenanthroline]·H2O - Mosconi, Natalia Ester (2021)
Fungal infections are still a major problem. Some limitations of current antifungals (toxicity, fungal resistance) require the search for new drugs. The interest in metal–sulfanilamide derivatives was stimulated by the successful introduction of a silver-sulfadiazine complex, yet in current use, to prevent microbial infections during burn treatment of both humans and animals. Sulfadimethoxine (HSDM) is used in medicine, most frequently veterinary, to treat many infections, such as respiratory, urinary, etc. In this work we report the synthesis, characterization by elemental analysis, FTIR, 1H NMR and 13C NMR spectra of the heteroleptic complexes [Ag3SDM(SCN)2]·H2O and [Ag2(SDM)2o-phenanthroline]·H2O, named as AgSDM-SCN and AgSDM-phen, respectively, and the biological properties (lipophilicity, antifungal, phyto, cyto and genotoxicity) of AgSDM-SCN, AgSDM-phen and the homoleptic one: AgSDM. 1H NMR spectra show that the sulfonamide moiety loses its acidic proton in both complexes, in agreement with the FTIR results. The three complexes showed a moderate antifungal activity, mainly against the yeasts Candida albicans, C. tropicalis and Cryptococcus neoformans. None of the tested fungi was inhibited by the free ligand. Lipophilicity: log Koctanol/water values were 0.80, 0.84, 0.85, 0.94 and 0.43 for HSDM, NaSDM, AgSDM, AgSDM-SCN and AgSDM-phen respectively, similarly to another sulfa-metal complexes. No genotoxicity or cytotoxicity were observed for AgSDM and AgSDM-SCN in the Allium cepa test, different from AgSDM-phen. Given these results, the studied complexes could be good candidates for further pharmaceutical studies.